Peningkatan Literasi Keuangan Masyarakat Melalui Sosialisasi Manajemen Keuangan Keluarga - Farhan Ahmad Hanafi; Qurtubi Qurtubi; Syarif Hidayat Hasibuan (Universitas Islam Indonesia, 2024)
The majority of the livelihoods of the people of Kenaran Hamlet are vegetable farmers and itinerant vegetable traders. In facing market realities, they are often disadvantaged by a significant decline in vegetable prices due to abundant supply. Knowledge about financial literacy and sound financial management is needed to address this wisely. To realize this, community service activities must educate the community to make their lives more economically prosperous. Departing from this, a family financial management socialization program was created to improve residents' financial literacy. This program was carried out in several stages: observation, program preparation, socialization, and evaluation. The result of this program is the local community's understanding of sound financial management and increased financial literacy to achieve economic prosperity.